Comparison of Antibacterial Effectiveness of Rambutan Leaf Extract (Nephelium lappaceum L.) and Tin Leaf Extract (Ficus carica L.) to Streptococcus mutans - Member Reni Purba; Dian Soraya Tanjung; Rona Angelin Purba (HM Publisher, 2023)
Background: Caries is an infectious disease accompanied by damage to the surface tissue of enamel, dentin and extends toward the pulp. Microorganisms that have a role in the formation of caries, namely Streptococcus mutans. Rambutan leaves and tin leaves are plants that have an antibacterial effect. This study aimed to compare the antibacterial effects of rambutan and tin leaves on the bacteria Streptococcus mutans. Methods: In vitro experimental studies. A total of 30 petri dishes that have been added 1-2 ose of bacterial culture Streptococcus mutans and MHA (mueller hinton agar) were used in this study, with 10 test groups, namely 2 control groups, 4 rambutan leaves extract test groups, and 4 tin leaves extract test groups. Data analysis was carried out with the help of SPSS using univariate and bivariate. Results: Extracts of rambutan leaves and tin leaves show the ability to inhibit the bacterial growth of Streptococcus mutans, along with increasing the dose of the extract. However, the inhibition ability of tin leaf extract was not as great as that of rambutan leaf extract at the same concentration. Conclusion: Rambutan leaf extract (Nephelium lappaceum L.) has effectiveness as an antibacterial Streptococcus mutans more optimal than tin leaf extract (Ficus carica L.).